A feasibility study on Elevate Prone Stander - Custodio, Benette; Dorde, Winnie; Millare, Lucky Joy; Panghulan, Abegail
The project is about the feasibility study of mass producing Elevate Prone Stander in the local market by designing and developing an affordable, quality, and ergonomic assistive device for Filipino children. It involves a marketing analysis, technical analysis, organizational analysis, financial analysis and socio-economic analysis. Through the marketing analysis, the need for Elevate prone stander of Filipino patients with cerebral palsy and other related postural problems (CPORPP) was established. The National Capital Region (NCR) which has the highest Cerebral palsy cases was the chosen target market. The demand from this market includes the demand from hospitals; demand from NGO's which will help 30",6 of the poorest low income class in NCR and personal usage from 100",6 high income class, 75% middle income class and 50% low income classes. It was also recognized that the market is still young and untapped because there are hardly any competitors that will pose threat to the product. The estimated production for five years is computed and it ranges from 463 to 607 units per year. The marketing strategies were also planned; these include vertical marketing system for placement strategy, different promotion and advertisement strategies. The sales plan will rely mainly on direct selling and this will cost to about Php327, 750 to Php439,250 for the first five years. Specifications and detailed flow charts for the manufacturing of Elevate are described in the technical study. The machine, raw materials and manpower requirements for the five year were determined. The company will be involved with the final assembly only. The main parts will be outsourced and all suppliers are found locally. The chosen plant location to be rented is in Tondo, Manila. Facility layout was created using traditional layout planning. Expenses were determined and the production costs were estimated at PhpS,638,284.96 to PhpS,699,589.96 for the first five years. The working capital was computed at Php9,077,534.96 and the total project cost at Php 10, 257,939. 96. In the organizational and management study, a detailed organizational plan and effective management structure in mass-producing the Elevate Prone Stander is formulated. The company that will sell and produce Elevate prone stander is chosen to be a non-stock corporation. Seven employees forms the comprehensive organizational chart. The functions and job description for the positions in the organization were defined. Compensations of employees were computed using the guidelines set by the government and prevailing salary standards for similar starting companies. Estimated salaries amount to a total of Php. 1,385,494 every year. In the financial study, the project cost is planned to be financed both by the Development Bank of the Philippines (DBP) and the company itself. Positive and increasing trend in the company's net income and cash flow projections were presented in the financial statements. The financial ratios reveal a stable financial position for the company. The computed net present value of Php 165,726.03 and internal rate of return of 37.34% > MARR @30% prove that the project is an acceptable venture. The payback period is 2.10 years. The company is proven to operate profitably, withstand adversity, generate sufficient cash, acceptable return on investment of the financiers and protects the investors and services its debts. The production and marketing of the ELEVATE Prone Stander is proven to be advantageous to the economy and society in the social profitability study. This is through the company's profitability as shown by the net present worth and IRR, taxes which will increase in revenue for the Government, provision jobs for qualified personnel, local supplier benefits, and other entities and businesses such as MERALCO, SSS, PAG-IBIG, GLOBE, MWSS,etc. Thus, the production and marketing of Elevate Prone Stander is feasible. And the primary aim of determining the feasibility of producing Elevate Prone Stander which will be very affordable for the families of disabled Filipino children was attained.